Computer system to optimize the attendance control of students of Universidad de Huanuco - López De La Cruz, Edgardo Cristiam Iván (2019)
Objective. To implement a Computer System to optimize the attendance control process of students of School of Systems and Computer Engineering from the Department of Engineering of Universidad de Huanuco, 2018. Methods. The research had an application level, of a technological type because information and communication technology were used for the development and application of this research. A pre-experimental design was used and it was applied in the same group with a pre-test and post-test. Population comprised of 12 students and 245 teachers from the Department of Engineering. The sample was determined in a non-probabilistic way, based on the number of users of the system of the School of Systems and Computer Engineering. Results. The optimization of the attendance control process of students of the School of Systems and Computer Engineering was demonstrated. In a pre-test, only 2.4 % of survey respondents chose very good among other options in the scale of the evaluation instrument. On the other hand, the post-test had a higher level of acceptance 91 %. They chose very good among other options in the scale. This showed an increase of 88.6 %. Conclusion. The process of attendance control of students of the School of Systems and Computer Engineering from the Department of Engineering of Universidad de Huanuco has been optimized, through implementation of a computer system. It was possible due to the use of a mobile application.